Hemilamprops chilensis sp. nov. (Crustacea: Cumacea: Lampropidae) from the coast of Chile, with a key to the Chilean Lampropidae and remarks on the status of H. ultimaespei Zimmer, 1921 and H. lotusae Băcescu, 1969 - Gerken, Sarah; Haye, Pilar A. (Zootaxa, 2018)
A new species is described, Hemilamprops chilensis, from Chile. The new species was collected at several localities, from Bahia Herradura in the central part of the country, to Ancud on the island of Chiloe in the south. The depth of collection ranged from 0–30 m. The species with the closest affinity to H. chilensis is the South African species, H. glabrus Day, 1978. The new species is distinguished from all other Hemilamprops by the combination of a short lateral ridge anteriorly on the carapace, maxilliped 3 with the basis much longer than the remainder of the appendage, and the telson bearing 3 terminal setae and 2 pairs of small lateral setae. The identities of H. ultimaespei and H. lotusae are fixed by lectotype and neotype designation, respectively. The lectotype of H. ultimaespei is selected as the neotype of H. lotusae, making H. lotusae a junior objective synonym of H. ultimaespei.